Studi Laju Perubahan Garis Pantai di Pesisir Tenggara Bali Menggunakan Citra Satelit Landsat (Studi Kasus Kabupaten Gianyar dan Klungkung) - I Nengah Jaya Nugraha; I Wayan Gede Astawa Karang; I Gusti Bagus Sila Dharma (Journal of Marine and Aquatic Sciences, 2017)
Erosion and abrasion are the events that led to the beach shoreline position changes. The impact of climate change is the rise in sea level also causes changes in the coastline. South East coast of Bali, especially along the coast Gianyar and Klungkung changing coastline. This study aims to identify and calculate the rate of shoreline change in Gianyar and Klungkung from 1995 to 2015. The study was a preliminary information shoreline change and do not analyze the causes such as tides, currents, waves, and wind. The method used remote sensing analysis with the extraction of the coastline from the Landsat 5 satellite images in 1995, Landsat 7 in 2005, and Landsat 8 2015. Landsat imagery analyzed by a combination of methods approach the threshold and band ratio of wave infrared and green. Image processing using software Quantum GIS 2.8 and System for Automated Geoscientific Analyses (SAGA) GIS 2.2, extention Digintal Shoreline Analysis System (DSAS) to make calculations transect coastline. The results of the analysis of overlaying identify coastline in Gianyar and Klungkung change at a rate that varies every village. The rate of change of coastline in Gianyar due to accretion between 0.5096 - 8.6074 m / yr, while due to erosion between -3.7343 to -1.3201 m / yr. The rate of change in Klungkung regency coastline due to accretion between 0.6337 - 2.6875 m / yr, while due to erosion between -8.8795 to -0.8833 m / yr.